Considerable variation in the 95-95-95 targets accomplishment between children and adults might delay achievement of set targets - Kulohoma, Benard W.; Wesonga, Colette S. A. (Frontiers in Public Health, 2025)
Despite a significant reduction in the global HIV disease prevalence in recent years, children under 15 years of age still account for 3% of people living with HIV, 9% of new incidence, and 12% of AIDS-related deaths. Although there is increased access and use of antiretroviral drugs, children under 1 year in resource-poor settings with a high HIV disease burden remain vulnerable due to poor initiation of these critical interventions impeding progress to meet the 95–95–95 targets. There are renewed efforts to ensure that exposed children under 15 years are not left behind by scaling diagnostics and clinical management in the most affected communities. However, gaps remain in the integration of these services into maternal, child, and adolescent healthcare services within these communities, resulting in only 67% of HIV-exposed infants being tested within 2 months of birth, globally in 2023. Consequently, only 29% of all exposed children under 15 years were initiated in antiretroviral treatment before their 5th birthday in 2023. There are successes for adults aged 15 years and above, but children under 15 years risk being left behind in achieving the 95–95–95 targets. In this study, we review efforts made to reduce these substantial regional variations when comparing progress made between children under 15 years and adults and highlight gaps that might impede achievement of the 95–95–95 targets among children.